2018
DOI: 10.1111/jocn.14563
|View full text |Cite
|
Sign up to set email alerts
|

Stroke survivors’ experiences transitioning from hospital to home

Abstract: Adjusting to life after a stroke during the first 4 weeks after discharge home is an in individualised experience. For the complex psychosocial and physical needs of ischaemic stroke survivors, nurses can play an important role beyond symptom management by fostering a dynamic relationship through individualised transitional care based on ischaemic stroke survivors experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 35 publications
10
38
0
Order By: Relevance
“…When examining the sociodemographic variables, we found that the study sample was similar to that of other studies, in which men at the transition from adulthood to older adulthood with low level of education were predominant (Benjamin et al, 2019; Connolly & Mahoney, 2018; Hebel, Bieniaszewski, & Kowalewski, 2014; Liu & Lou, 2019). Furthermore, we found similarities with regard to the clinical data, for which we observed a history of hypertension and TIA, the presence of ischemic stroke as the primary stroke type, low disease severity at discharge according to the NIHSS and low current functional impairment (Benjamin et al, 2019; Connolly & Mahoney, 2018; Hebel et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…When examining the sociodemographic variables, we found that the study sample was similar to that of other studies, in which men at the transition from adulthood to older adulthood with low level of education were predominant (Benjamin et al, 2019; Connolly & Mahoney, 2018; Hebel, Bieniaszewski, & Kowalewski, 2014; Liu & Lou, 2019). Furthermore, we found similarities with regard to the clinical data, for which we observed a history of hypertension and TIA, the presence of ischemic stroke as the primary stroke type, low disease severity at discharge according to the NIHSS and low current functional impairment (Benjamin et al, 2019; Connolly & Mahoney, 2018; Hebel et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…In this cohort, it is likely that post-stroke cognitive impairment, new physical disability and the recent transition home contributed to these reduced scores. This finding supports the need for ongoing intensive home-based rehabilitation post stroke during periods of challenge and adaptation (Connolly and Mahoney, 2018;Winstein et al, 2016). The high proportion of accuracy errors compared to the other error types indicated that participants were able to perform the key steps of the task but had difficulty applying cognitive strategies to do so effectively.…”
Section: Discussionsupporting
confidence: 65%
“…After the protection and structure of the hospital environment, the transition home can be a challenging period for the stroke survivor and their family (van der Wijst et al, 2014;Winstein et al, 2016) due to the dynamic home environment and subsequent increased demands on cognitive strategy application (Burns and Neville, 2016;Stigen et al, 2019). Whilst identifying advantages of ESD and the home environment (Lou et al, 2017), stroke survivors have also reported challenges with transition home due to incongruency between anticipated and real level of occupational performance and cognition (Connolly and Mahoney, 2018;Lou et al, 2017). This cognitive challenge may be magnified by shorter inpatient length of stays (Chouliara et al, 2014), stroke survivors not receiving standardised cognitive assessment during their inpatient admission and hospital-based assessments being a poor predictor of real-world performance (Morrison et al, 2015;Pilegaard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It often leads to lifelong critical disability [1]. All stroke survivors are at risk of complications during recovery, regardless of stroke severity [2]. Patients' initial experiences after the onset of stroke are well described in various studies [3, 4].…”
Section: Introductionmentioning
confidence: 99%